Students’ Difficulties in Learning English Pronunciation - Yasinta Wulandari; Asfi Aniuranti; M. Happy Nur Tsani (ELT in Focus, 2022)
Pronunciation is one of important language elements that should be mastered by the English language users. By producing good pronunciation, students can avoid misunderstanding in communication and they can deliver the message clearly. However, many EFL learners especially Indonesia have not shown good pronunciation. Many English learners still encounter difficulties in learning pronunciation. This study employs a qualitative descriptive method with aim to find the students’ difficulties in learning pronunciation. Questionnaire is used to investigate the students’ difficulties in learning pronunciation. The findings show that students have good perception about the importance of English pronunciation, they are also well motivated to improve their pronunciation. The environment also allows students to get the best exposure of pronunciation since the lecturers give good examples of pronunciation and opportunity to practice their pronunciation. The lecturers also give feedback both in pronunciation class and other classes. However, the students still find difficulties in learning pronunciation. They still find difficulties in recognition of native English pronunciation. They do not know how to use phonemic symbols in pronunciation, they also get nervous in production, and feel ashamed to produce incorrect pronunciation.